The Concept of Forgiveness of Victims against Perpetrators in the Islamic Legal System According to the Qur'an - Nuraini Nuraini; Rizqi Mulia Abadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Most people understand that forgiveness must begin with an apology first, even though in the Qur'an it is explained that forgiveness begins with forgiveness before an apology. This research uses library research method. Data analysis used the maudhu'i interpretation method. The results of the study found 34 verses about forgiveness in different suras. Of the 34 verses, the author takes six verses in examining the problem in question, namely surah al-A'raf: 199, surah Ali 'Imran: 134, surah al-Shura: 40, surah al-Nur: 22, surah al-Baqarah: 178 and Surah Ali 'Imran verse 159. These verses were chosen because they are closely related to the discussion being studied. The study of the Qur'anic verses revealed that the concept of forgiveness offered is to forgive the perpetrators of crimes before an apology from the perpetrators arrives. From the interpretation of Ibn Kathir and M. Quraish Shihab it is known that Allah SWT. commanded His servant to become a person who forgives, it is a highly glorified trait. With this attitude embedded in a person, it will create a prosperous, peaceful and strong ukhuwah life. the concept of forgiveness, namely: First; Conditional forgiveness. Second; Forgive without waiting for an apology. Third; Debate in solving cases. Fourth; Be a forgiving person. Fifth; do good to the perpetrator. Sixth; Forgiveness does not demean someone. Sixth; Forgiveness does not demean someone. Sixth; Forgiveness does not demean someone.